Opistognathus ensiferus, a new species of jawfish (Opistognathidae) from the Gulf of Mannar, India, with redescription of O. solorensis Bleeker - Smith-Vaniz, William F. (Zootaxa, 2016)
A new species of jawfish, Opistognathus ensiferus n. sp., is described based on a single specimen from Manauli Reef in the Gulf of Mannar, India. It is a member of a species group that also includes Opistognathus solorensis Bleeker (Indonesia, Philippines, Taiwan and Palau) and O. verecundus Smith-Vaniz (northwestern Australia). From these two species O. ensiferus n. sp. differs in lacking dark oral pigmentation, except inner lining of upper jaw and adjacent membranes with a single dark stripe (vs. two stripes) and in having a lateral line ending below the 6th or 7th segmented dorsal-fin ray (vs. below the 1st to 4th ray). Opistognathus solorensis is redescribed and in the absence of extant type specimens a neotype is designated. Two strikingly different color morphs are documented for O. solorensis, including the less common one which is almost entirely yellow.